Busca de biomarcadores como indicadores do mecanismo de defesa da laranja pera à infecção de CVC através de análise metabonômica - Cerqueira, Cristovam do Nascimento (2016)
This paper describes the search and identification of probable biomarkers related to defense mechanism triggered by the plants to the infection process of Xylella fastidiosa, bacterium that causes Citrus Variegated Chlorosis (CVC), which is one of the most serious diseases that cause losses in the Brazilian citrus industry.For this purpose, it was evaluated by chemometric tools and analytical methods such as, UPLC-ESI-QTof the metabolic variation between seedlings developed by seed ofCitrus sinensis and C. limonia in the search and identification of biomarkers that could indicate the biochemical mechanism that would explain the resistance of C. limoniaagainst CVC.It was also analyzed seedilings, healthy and infected by X fastidiosa,of C. sinensisgraftedon C. limonia in the searching of biomarkers to attempt to associate them with the metabolic routes and provide a defense mechanism explanation these seedilings against the infection process. For this objective to be achieved it has been used online databases as was also set up a secondary metabolite database of Citrus genus with all the metabolites recorded in the literature, enabling better selection and easier identification of these biomarkers. The chemometric tools (PCA, HCA, S-plot) applied to the data obtained in studies of LC-MS, discriminating 47compounds, of which 35were putatively identified as being responsible for C. limonia resistance process against to the bacterial infection process, where proposes that the chemical aspects related to this characteristic is due to the high concentrations of coumarinsSeselin and Xanthyletin in the leaves that would prevent the initial bacterial adhesion process in xilematcs vessels as well as proposes the highest flavonoid concentrations that would play the role of bactericidal agent. In the analysis of healthy and infected grafts it was possible to discriminate 41 compounds, of which 30were putatively identified, where the analysis of metabolites aspects indicated that during the infectious process there is a high expression of the family genes polyketide synthase which is responsible for high production alkaloids acridonicos in the infected roots and stems as well as in infected leaves of flavonoids.It may be associated as a defense mechanism.